Crisis and Competition in Expert Organizational Decision Making: Credit-Rating Agencies and Their Response to Turbulence in Emerging Economies - Vaaler, Paul M.; McNamara, Gerry (Organization Science, 2004)
Firms often delegate elements of strategic decisions to outside experts who promise objective assessments, which are especially valuable in unstable environments. However experts themselves may be prone to skewed decision making as the stability of their own industry environment changes and as their positioning within the industry shifts. We examine this possibility in the context of expert credit-rating agencies (“agencies”) and their risk ratings of emerging-market sovereign borrowers (“ratings”) published from 1987 to 1998, a period that includes both industry stability (1987–1996) and industry turbulence set off by financial crises in several emerging-market countries (1997–1998). After controlling for macroeconomic and related objective risk factors linked to the sovereigns themselves, we find several points: (1) agency ratings during crisis-induced industry turbulence are negatively skewed, indicating undue pessimism among these experts, in line with decision-making perspectives predicting negative reaction by experts in an effort to retain legitimacy with salient stakeholders, in this case, investors and public regulators; (2) this negative shift is greater for incumbent firms and regionally focused firms, possibly because of the loss of previous informational advantages; and (3) this negative shift during crisis-induced turbulence is greater as industry rivalry among these experts increases in particular market segments, possibly indicating the development of competitive bandwagons among experts. Together, our results suggest that objective assessments by expert organizations are vulnerable to substantial distortion from the confluent effects of industry instability and expert positioning within the industry, particularly positioning affecting rivalry among experts. Ironically, experts may be most likely to mislead clients in unstable industry environments when experts command greater attention and should show greater fidelity to disinterested objectivity.